Preface. (8th January 2013) - Leonard, David K.
Abstract How do, could and should the various institutions responsible for the production of security and the management of conflict in Tropical African societies evolve in response to the presence of violent conflict? The research reported in this issue of the IDS Bulletin is built on the observation that all governance (especially in Africa) is multilevelled and networked – from the village to the international organisation, and well beyond what is specified in formal government structures. Thus the focus must be not only on the ways in which key conflict‐management institutions evolve themselves but also on the changing ways in which the networks in which they are embedded actually operate.